2015
DOI: 10.2224/sbp.2015.43.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Leadership and Followers' Attitudes Toward Corporate Social Responsibility: The Role of Perceived Ethical Work Climate

Abstract: Increasing attention is being paid to how leaders influence followers' perceptions of the importance of ethics and corporate social responsibility (CSR) for organizational effectiveness. However, few researchers have conducted empirical investigations into the impact of leadership style on followers' attitudes toward CSR. In this study, participants comprised 313 employees of 5 large financial and banking service firms in Korea. Results indicated that ethical leadership was strongly associated with followers' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 21 publications
3
44
0
Order By: Relevance
“…Brown, Trevin˜o, and Harrison () conclude that EL takes care of everybody who is directly or indirectly influenced by firm's operations. Nevertheless, financial crisis, downturn in the economy, and repeated scandals in government and firms have led academicians and policy makers to analyze more in‐depth how leaders can enrich CSR engagement, employee loyalty, performance, and commitment (Choi, Ullah, & Kwak, ). In summary, Table reports the main relationships among CSR and firm performance.…”
Section: Literature Review On El Csr and Fpmentioning
confidence: 99%
See 1 more Smart Citation
“…Brown, Trevin˜o, and Harrison () conclude that EL takes care of everybody who is directly or indirectly influenced by firm's operations. Nevertheless, financial crisis, downturn in the economy, and repeated scandals in government and firms have led academicians and policy makers to analyze more in‐depth how leaders can enrich CSR engagement, employee loyalty, performance, and commitment (Choi, Ullah, & Kwak, ). In summary, Table reports the main relationships among CSR and firm performance.…”
Section: Literature Review On El Csr and Fpmentioning
confidence: 99%
“…Brown, Trevin˜o, and Harrison (2005) conclude that EL takes care of everybody who is directly or indirectly influenced by firm's operations. Nevertheless, financial crisis, downturn in the (Choi, Ullah, & Kwak, 2015). In summary, Table 5 reports the main relationships among CSR and firm performance.…”
Section: Literature Review On El Csr and Fpmentioning
confidence: 99%
“…Some examples [23] have shown that organizations benefit from training company executives. For example, some studies have demonstrated a positive relationship between worker training and desirable psychosocial effects, such as employee motivation [24,25], job satisfaction [26], and company profit [27]. In Spain, Escartín [28] found that training on psychosocial risks was a precursor to several quantifiable improvements in the working environment.…”
Section: Training On Psychosocial Risks At Workmentioning
confidence: 99%
“…Further, Carpenter and Reimers (2005) found that managers’ attitudes, shaped by the tone set by top executives, significantly influence managers’ decisions to behave unethically. Many researchers investigated the effects of both ethical leadership and ethical climate on employees’ antisocial behaviors (Elçi et al 2013), misconduct (Mayer et al 2010), attitudes toward corporate social responsibility (Choi et al 2015), and organizational commitment (Constandt et al 2016). Ethical sensitivity, which is the basic logical starting point of all types of ethical or unethical behaviors, will also be affected by the interrelationship of ethical leadership and ethical climate.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%